Forced Migrants, Media, and Securitization: Making Sense of the Changing Representations of Transit Asylum Seekers in Indonesian Print Media - Antony Lee (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2017)
This paper aims to explain how and why the representations of transit forced migrants in Indonesian major print media were vastly different within two time spans: (1) during the arrivals of the Indochinese refugees in 1975-1996 and (2) in the period of the new generations of refugees from Middle Eastern and South Asian countries in 1997-2013. Employing media content analysis of 216 news articles from three major print media in Indonesia, this study found out that the Indochinese refugees were portrayed with positive labels and thus, mainly discussed in connection with the non-security theme. In contrast, the new generations of forced migrants were portrayed with negative labels such as ‘illegal immigrants’ and were framed as security threats. Grounded within Securitization Theory, this paper thus argues that the changing representations were caused by the securitizing move made by specialized agencies in Indonesia.